Combinations of Verbal and Non-Verbal Message Codes on Reddit - Andrey G. Fomin; Natalia A. Smakotina (Виртуальная коммуникация и социальные сети)
Reddit.com provides an excellent example of interactive digital communication. Reddit comments and posts organize information in line with certain rules of coding and decoding. They convey meanings by semiotically heterogeneous verbal and non-verbal means. The article describes various combinations of communication codes that act as a communication tool, i.e., verbal, linguistic, verbal-visual, verbal-auditory, and verbal-kinesthetic. The research objective was to identify the structural and communicative organization of semiotically heterogeneous texts in the dynamics of interpersonal Internet communication. The research involved standard methods and covered publications on Reddit.com connected with the activities of the SpaceX corporation. The combinatorics of message codes formed a set of modes and modalities. They were actualized as a model of Internet communication with speech events in a communicative act subjected to regulation and modification, i.e., confirmation / refutation, approval, accusation, ignoring, etc., depending on the channel of perception and understanding. The combinatorics of verbal and non-verbal communication codes made it possible to model and classify the information and communication organization of online publications of the SpaceX business subreddit. The integration of the language system into complex semiotic systems helps to describe mental processes and human cognitive activity. It shapes new views and beliefs, as well as increases the effectiveness of communication.